Recreational Physical Activity Improves Adherence and Dropout in a Non-Intensive Behavioral Intervention for Adolescents With Obesity - Lofrano-Prado, Mara Cristina; Donato Junior, Jose; Lambertucci, Adriana Carneiro; Lambertucci, Rafael Herling; Malik, Neal; Ritti-Dias, Raphael Mendes; Correia, Marilia Almeida; Botero, João Paulo; Prado, Wagner L. (Research quarterly for exercise and sport, 2022)
Purpose: The aim of this study was to compare adherence and dropout rates in adolescents with obesity participating in a behavioral-counseling intervention with or without recreational physical activity (PA). Material and methods: Seventy-four adolescents (13 to 18y, 40 girls and 34 boys) with obesity (body mass index [BMI] z-score ≥ 2.0) were randomized into a counseling group (CG; n = 37) and a counseling + recreational physical activity group (CPAG; n = 37). Adolescents from both groups received behavioral counseling once a week for 12 weeks and monthly for an additional 12 weeks. CPAG adolescents participated in supervised recreational physical activity sessions twice a week for 12 weeks. Body composition, body image dissatisfaction, symptoms of depression, binge eating, bulimia, anorexia and quality of life were assessed at baseline and after 24-weeks. Result: The dropout rate was 2.73 times higher in adolescents from CG compared to CPAG (χ 2 = 4.48; p = .034; R 2 McF = 0.044). Girls were 2.56 times more likely to withdraw when compared to boys (χ 2 = 3.86; p = .049; R 2 McF = 0.038). Binomial logistic regression which incorporated sex, intervention group, BMI z-score and BSQ score at baseline (R 2 McF = 0.177) explained 75% of the dropout rate. Both interventions were effective in reducing waist circumference (p < .01) and improving quality of life, symptoms of depression, bulimia and binge eating (p < .01). Conclusion: Incorporating a recreational physical activity component to a non-intensive behavioral intervention may be a feasible strategy to reduce dropout rates in adolescents with obesity seeking treatment.